PENGEMBANGAN PERANGKAT LUNAK UNTUK AKUISISI DATA KONSUMSI DAYA LISTRIK DARI POWER METER - Ginting, Ignatius; Mulyadi, Melisa; Wijayanti, Linda; Manalu, Ferry Rippun Gideon (Jurnal Elektro, 2024)
Technological developments make it possible to monitor electricity consumption in real-time via the internet. The system developed uses a power meter to collect data, Python to process data and IoT connectivity via NodeMCU ESP8266 to send data to the internet. Python is used so that measurement data can be processed and presented in an easy-to-understand format. The test results show that electrical data measurements can be displayed with an error ranging from 0.04% -11.56%. This is because there is a delay from the time the power meter is measured until the data is displayed on ThingSpeak.